Why people do, or do not, immediately contact emergency medical services following the onset of acute stroke: qualitative interview study. - Joan E Mackintosh; Madeleine J Murtagh; Helen Rodgers; Richard G Thomson; Gary A Ford; Martin White (PLoS ONE)
Objectives To identify the reasons why individuals contact, or delay contacting, emergency medical services in response to stroke symptoms. Design Qualitative interview study with a purposive sample of stroke patients and witnesses, selected according to method of accessing medical care and the time taken to do so. Data were analysed using the Framework approach. Setting Area covered by three acute stroke units in the north east of England. Participants Nineteen stroke patients and 26 witnesses who had called for help following the onset of stroke symptoms. Results Factors influencing who called emergency medical services and when they called included stroke severity, how people made sense of symptoms and their level of motivation to seek help. Fear of the consequences of stroke, including future dependence or disruption to family life, previous negative experience of hospitals, or involving a friend or relations in the decision to access medical services, all resulted in delayed admission. Lack of knowledge of stroke symptoms was also an important determinant. Perceptions of the remit of medical services were a major cause of delays in admission, with many people believing the most appropriate action was to telephone their GP. Variations in the response of primary care teams to acute stroke symptoms were also evident. Conclusions The factors influencing help-seeking decisions are complex. There remains a need to improve recognition by patients, witnesses and health care staff of the need to treat stroke as a medical emergency by calling emergency medical services, as well as increasing knowledge of symptoms of stroke among patients and potential witnesses. Fear, denial and reticence to impose on others hinders the process of seeking help and will need addressing specifically with appropriate interventions. Variability in how primary care services respond to stroke needs further investigation to inform interventions to promote best practice. Trial registration UK Clinical Research Network UKCRN 6590.